The influence of US hegemony on the South African anti-trafficking in persons movement - Moodley, Rene Puzzo (My University, 2016)
The contemporary movement to end human trafficking rose to prominence in the early to mid 1990s. Following the fall of the Soviet Union, the US found itself in need of new tools to extend its global reach. This report argues that the modern day movement to abolish human trafficking is one of the new tools used to advance US hegemony. South Africa provides a unique context for the study of how US hegemony has been employed through this movement. The rise of this movement coincided with the rise of democracy in the rainbow nation. Under Apartheid, US policy toward South Africa was linked with the fight against communism. The US would channel money to black liberation movements in order to shape their views in a pro-western direction. South Africa was considered important to US economic interests and prosperity. With the communist enemy gone, the US has employed new tools to influence ideology, policy and legislation. Through studying the Anti-Trafficking in Persons (TIP) movement in the South African context, this report analyzes how the movement is a tool of hegemony. Tactics used to gain public consent and legitimize the cause are uncovered, as are coercive measures used to stronghold the South African government to comply with the US.
A dissertation presented in partial fulfilment of the requirements for the Masters of Arts Degree in Political Studies, Faculty of the Humanities at the University of the Witwatersrand, Johannesburg, 2016
Keywords: Human trafficking--South Africa; Hegemony--United States.; South Africa--Relations--United States; United States--Relations--South Africa